Effects of apnoea training on aerobic and anaerobic performance: A systematic review and meta-analysis - de Asís-Fernández, Francisco; Sereno, Daniel; Turner, Anthony P.; González-Mohíno, Fernando; González-Ravé, José María (Frontiers in Physiology, 2022)
Background Trained breath-hold divers have shown physiological adaptations that might improve athletes’ aerobic and anaerobic performance. Objective This study aimed to systematically review the scientific literature and perform a meta-analysis to assess the effects of voluntary apnoea training on markers of anaerobic and aerobic performance, such as blood lactate and VO2max. Methods A literature search on three databases (Web of Science, PubMed and SCOPUS) was conducted in March 2022. The inclusion criteria were 1) peer-reviewed journal publication; 2) clinical trials; 3) healthy humans; 4) effects of apnoea training; 5) variables included markers of aerobic or anaerobic performance, such as lactate and VO2max. Results 545 manuscripts were identified following database examination. Only seven studies met the inclusion criteria and were, therefore, included in the meta-analysis. 126 participants were allocated to either voluntary apnoea training (ApT; n = 64) or normal breathing (NB; n = 63). Meta-analysis on the included studies demonstrated that ApT increased the peak blood lactate concentration more than NB (MD = 1.89 mmol*L−1 [95% CI 1.05, 2.73], z = 4.40, p < 0.0001). In contrast, there were no statistically significant effects of ApT on VO2max (MD = 0.89 ml*kg−1*min−1 [95% CI −1.23, 3.01], z = 0.82, p = 0.41). Conclusion ApT might be an alternative strategy to enhace anaerobic performance associated with increased maximum blood lactate; however, we did not find evidence of ApT effects on physiological aerobic markers, such as VO2max. Systematic Review Registration: [PRISMA], identifier [registration number].